(untitled) (Medical Forum Monthly, 2020)
Objective: To determine vitamin cobalamin (VC) in metformin treated type 2 diabetics compared to no metformin treated type 2 diabetics. Study Design: Observational study Place and Duration of Study: This study was conducted at the Isra University Hospital, from March 2019 to February 2020. Materials and Methods: A sample of 221 diabetics taking metformin (Group A- cases) and 200 diabetics (no metformin) (Group B - control) were selected through non-probability convenient sampling. Blood was centrifuged to get sera for analysis. Cobalamin was detected by ELISA assay kit (Chemiluminescence Technique). Data was analyzed and tabulated on SPSS (version 21.0) at 95% CI. Results: Mean VC levels in group A (diabetics taking metformin) and group B (diabetic not taking metformin) were found at 139.5±15.7 and 302.5±58.51 pg/dl respectively (P=0.0001). VC deficiency was found in 83.3% in diabetics taking metformin compared to 71.5% in diabetic not taking metformin. Conclusion: We found cobalamin deficiency in 83.3% diabetics taking metformin compared to 71.5% diabetic not taking metformin.